The impact of type 2 diabetes and body mass index on cerebral structure is modulated by brain reserve. (20th September 2018) - Walsh, E. I.; Shaw, M.; Sachdev, P.; Anstey, K. J.; Cherbuin, N.
Abstract : Background and purpose: Body mass index (BMI), hyperglycaemia and type 2 diabetes and their interactive effects are associated with brain volume atrophy in ageing. It remains to be established if these risk factors are particularly concerning in individuals with high or low brain volumes. Methods: Demographics, venous blood and magnetic resonance imaging data were collected for 494 healthy community‐living adults aged 53–78 (mean 65) years, as part of the Personality and Total Health Through Life study. Associations between BMI, blood glucose, diabetes status and brain volume (whole brain, grey matter, white matter and subcortical structures) were investigated using quantile regression. Results: Quantile regression revealed vulnerability to BMI × glucose interactions particularly in lower volumes and significant main effects for type 2 diabetes particularly in higher volumes. Diabetes was most strongly associated with brain volumes. The association between BMI, blood glucose and diabetes was not consistent across the full range of brain volumes. Conclusion: Explicit investigation of the upper and lower boundaries of brain volume distributions was valuable. We found evidence of protective reserve from higher brain volumes and that a combination of high BMI and higher blood glucose was particularly concerning for individuals with lower brain volumes.